2009
DOI: 10.2139/ssrn.1460645
|View full text |Cite
|
Sign up to set email alerts
|

Volatility Spillovers between Stock and Currency Markets: Evidence from Emerging Eastern Europe

Abstract: The purpose of this study is threefold. First, we look at the linkages between Eastern European emerging equity markets and Russia. Second, we investigate the relationships between the currency markets of Poland, Hungary, Russia, and the Czech Republic. Finally, we examine the interdependence between Emerging Eastern European and Russian equity and currency markets. We estimate a bivariate GARCH-BEKK model proposed by Engle and Kroner (1995) using weekly returns. We find evidence of direct linkages between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 31 publications
3
35
1
2
Order By: Relevance
“…The unidirectional transmission of volatility between equity and currency market has been reported by following studies (Adjasi et al 2008;Antonakakis 2012;Beer and Hebein 2011;Chkili and Nguyen 2014;Ebrahim 2000;Fedorova and Saleem 2009;Kanas 2000;Kang and Yoon 2013;O'Donnell and Morales 2009;Okpara and Odionye 2012;Yang and Doong 2004;Yang and Chang 2008). Ebrahim (2000) empirically examined the flow of volatility of exchange rate on the developed equity markets.…”
Section: Review Of Literaturementioning
confidence: 94%
See 1 more Smart Citation
“…The unidirectional transmission of volatility between equity and currency market has been reported by following studies (Adjasi et al 2008;Antonakakis 2012;Beer and Hebein 2011;Chkili and Nguyen 2014;Ebrahim 2000;Fedorova and Saleem 2009;Kanas 2000;Kang and Yoon 2013;O'Donnell and Morales 2009;Okpara and Odionye 2012;Yang and Doong 2004;Yang and Chang 2008). Ebrahim (2000) empirically examined the flow of volatility of exchange rate on the developed equity markets.…”
Section: Review Of Literaturementioning
confidence: 94%
“…There are also number of studies of integration of foreign exchange market and stock market of developing countries (for example; Choi et al 2010;Kang and Yoon 2013;Mishra et al 2007;Morales 2008;O'Donnell and Morales 2009;Qayyum and Kamal 2006;Yang and Chang 2008). There are also some studies for emerging countries for instance (see, for examples; Adjasi et al 2008;Fedorova and Saleem 2009;Li and Majerowska 2008;Oberholzer and Boetticher 2015;Okpara and Odionye 2012;Walid et al 2011).…”
mentioning
confidence: 99%
“…Galloppo, Paimanova and Aliano (2015) focused on the transparency and efficiency of the Eastern European share markets. Fedorova and Saleem (2010) analysed the relations between Polish, Hungarian, Russian and Czech share and currency markets. Bota and Ormos (2014) analysed the weakform efficiency of the CEE share markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly to the authors' findings, no evidence was found of causality that ranges from foreign exchange market to stock market in the Czech Republic. Fedorova and Saleem (2010) also considered this topic using a bivariate GARCH-BEKK model and data span from January 1995 to December 2008. They documented unidirectional volatility spillover from currency markets to stock markets in Poland, Hungary and Russia.…”
Section: Panel B Ofmentioning
confidence: 99%